(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
This inquiry aims to disclose and describe parenthood standards underlying – and perpetuated by – legal regulation of medically assisted reproduction in France. To what extent did MAR French law detach the right to medical support to fulfil a desire for a child from traditional, biogenetically grounded, couple-centred, and gendered conceptions of parenthood? Do some parental projects remain explicitly or implicitly excluded by the rules regarding access to MAR and MAR procedures? This article provides a few answers through an analytical and socio-legal approach to MAR regulation in France in its recent developments.